E-learning Platform for Handpiece Care in Odontology (LACCEI, 2024)
The useful life of a handpiece depends significantly on the maintenance given by each odontologist. Not all odontologists perform these preventive maintenance routines correctly and consequently, there is an incidence of damaged handpieces. The objective of the project was to develop an e-learning platform regarding the handling and care of high-speed handpieces based on the study of odontologists in Tegucigalpa, Honduras. The development of this e-learning platform began with a bibliographical review and experts’ advice. A questionnaire was applied to investigate the current practices of odontologists in Tegucigalpa regarding the handling and care of high-speed handpieces. Then, parameters were defined for the selection of the software to develop this platform. Once the platform was developed, it was socialized. Odontologists in Tegucigalpa found that the average useful life of their high-speed handpieces is more than two years. However, only 31.8% of these odontologists base their maintenance routines on the manufacturer's instructions this indicates that the useful life could be shorter. The e-learning platform regarding the management and care of high-speed handpieces was developed based on the study of odontologists in Tegucigalpa. The content of the platform was defined by the lack of knowledge identified in the odontologists of Tegucigalpa and the opinion of biomedical engineers in the odontological area.